Application of Furcellaran Nanocomposite Film as Packaging of Cheese - Pluta-Kubica, Agnieszka; Jamróz, Ewelina; Khachatryan, Gohar; Florkiewicz, Adam; Kopel, Pavel (Polymers, 2021)
There is a serious need to develop and test new biodegradable packaging which could at least partially replace petroleum-based materials. Therefore, the objective of this work was to examine the influence of the recently developed furcellaran nanocomposite film with silver nanoparticles (obtained by an in situ method) on the quality properties of two cheese varieties: a rennet-curd (gouda) and an acid-curd (quark) cheese. The water content, physicochemical properties, microbiological and organoleptic quality of cheese, and migration of silver nanoparticles were examined. Both the number of Lactococcus and total bacteria count did not differ during storage of gouda regardless of the packaging applied. The number of Lactococcus decreased in analogous quark samples. The use of the film slowed down and inhibited the growth of yeast in gouda and quark, respectively. An inhibitory effect of this film on mold count was also observed; however, only regarding gouda. The level of silver migration was found to be lower in quark than in gouda. The film improved the microbiological quality of cheeses during storage. Consequently, it is worth continuing research for the improvement of this film in order to enable its use in everyday life.
Keywords: active packaging; gouda; quark; nanofiller; shelf life